Language in the Americas: Out of Beringia - Francis, Norbert (Universidad de Alcalá. Servicio de Publicaciones, 2021)
Linguistically, the Western Hemisphere harbors a great typological diversity, by sorne estimates, the greatest in the world. Controversy regarding classification aside, much work lies ahead to identify the movements up through to include the final leg of the journey of modern humans, in terms of distance travelled from our continent of origin, to Tierra del Fuego. This article will briefly summarize the advances that the language sciences have made in describing these migrations and the languages that accompanied them, to then discuss viable proposals for collaboration with other fields. Such an interdisciplinary program of study is necessary because the tools of linguistics do not suffice. Continuing work on the processes of origin, dispersion and convergence will help us better understand fundamental properties of language. Research on the description of individual languages and how they can be classified will contribute to this understanding. For speakers and students of the American languages, these advances will also contribute to the recovery of the cultural heritage that is associated with historical language change. Lingüísticamente, el hemisferio occidental alberga una gran diversidad tipológica, según algunas estimaciones, la más importante en el mundo. La controversia sobre las clasificaciones aparte, queda por delante mucha investigación para identificar los movimientos, incluyendo el último tramo de la migración de los humanos modernos, en términos de distancia transcurrida desde nuestra región de origen, hasta Tierra del Fuego. El presente artículo esbozará los avances en las ciencias del lenguaje en el estudio del movimiento de poblaciones y las lenguas que hablan, para luego abordar de tema de las propuestas para la colaboración con investigadores en otros campos. Tal programa de investigación interdisciplinario se perfila como necesario porque las herramientas de la lingüística no son suficientes. Futuros trabajos sobre los procesos de origen, dispersión y convergencias ayudarán a ...